LETTER FROM THE EDITOR-IN-CHIEF - Van Hai, Nong (Vietnam Journal of Biotechnology, 2022)
The year 2022 is the 20th on the path of Vietnam Journal of Biotechnology (VJBT) establishment and development. The VJBT has become a national prestigious leading scientific journal in biotechnology and related fields.Last year, new Editorial Board of VJBT for the 2021-2026 tenure has been strengthened. Notably, the Editorial Board now consists of 37 members, with the participation of 12 scientists from the institutions of Vietnam Academy of Science and Technology, 10 scientists from leading universities, research institutions and hospitals in the country. Especially, the new Editorial Board has invited 15 foreign and overseas Vietnamese scientists (The United States: 1, Germany: 2, Denmark: 1, Norway: 1, India: 1, Bangladesh: 1, Sri Lanka: 1, Japan: 3, Singapore: 1, Thailand: 2, and Philippines: 1). This is one of the important prerequisites for gradually improving quality and enhancing the visibility of VJBT for national and international readers.Implementing the project for enhancing Journal quality standards to match those of Scopus and/or Web of Science, starting form this year, VJBT decided to publish fully in English. Besides the hardcopy format, an electronic online edition is considered to appear very soon.Also, we regularly upgrade the Website for On-line submission and processing including reviewers’ reports and editorial decision on manuscripts. The Journal archives will be fully digitized and converted to Open Access for readers. From the number 1, volume 14, 2016 up to now, each published article has received a standard DOI.One of the important factors for the success of the Journal is the number and quality of manuscripts, so we hope to receive more and more high quality research papers from strong national and international research groups.The Editorial Board would like to thank our authors and readers for their continuous interests and contributions to VJBT in the past and look forward to your strong supports in the future.